2016
DOI: 10.17225/jhp00081
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status in children with haemophilia - a comparative study

Abstract: People with haemophilia may neglect their oral hygiene due to the fear of bleeding during brushing, leading to an increase in dental caries, gingivitis and periodontitis in this group. The available literature shows very few studies on the oral health status of children with haemophilia. The aim of the current study, therefore, was to assess the oral health status of children with haemophilia in comparison with healthy children. Data were collected from a study and control groups of haemophilic and healthy chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 13 publications
0
23
0
1
Order By: Relevance
“…The sample size of this study was the highest as compared to the previous studies that have evaluated the orodental status of subjects with coagulation disorders . A recent study by Babu et al . on 100 hemophilic patients included only the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The sample size of this study was the highest as compared to the previous studies that have evaluated the orodental status of subjects with coagulation disorders . A recent study by Babu et al . on 100 hemophilic patients included only the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies concluded that people with hemophilia had a better dentition with lesser caries experience when compared to age matched healthy individuals . Whereas some authors observed that individuals with hemophilia had a more caries prone dentition when compared to healthy population …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Trombosit agregasyonu üzerinde etkisi olduğu için aspirinden kaçınılır. 7 Sıklıkla görülen bu problemlerin yapılan bazı çalışmalarda daha kötü ağız sağlığına sebep olduğu 15,16 ve yaşam kalitesini düşürdüğü saptanmıştır. 5,14 Hem yaşam kalitesini yükseltmek, hem de tedavi ihtiya-cını azaltmak için hastaların oral hijyen eğitimi her zaman ön planda tutulmalıdır.…”
Section: Hemofili Hastalarında En Sık Görülen Oral Problemlerunclassified